P063 Pepse from the emergency department: reducing missed opportunities for patient follow up. (8th June 2017) - Megarity, Stephen; Rafferty, Paul; Quah, Say
Abstract : Introduction: PEPSE is one method of reducing HIV transmission in higher risk groups. It is commonplace for PEPSE to be delivered from the Emergency Department (ED) out-of-hours. PEPSE delivered outside of GUM can be met with challenges in regard to follow up; resulting in missed opportunities for health promotion, education and STI testing. Methods: Retrospective case-note review of ED episodes from 1/4/2015–31/3/2016. Demographic information and data collected compared with audible outcomes (BASHH 2015 PEP guidelines). Results: 37 patient episodes identified; 97% male with a mean age 28.2 years. 86% of these episodes occurred out-of-hours with 84% receiving PEPSE within recommended indications (standard 90%). 81% of patients prescribed PEPSE had an HIV test within 72hours (standard 100%). In regard to follow up, 59% of all patients attended for STI testing (standard 90%). There was a 9% rate of STIs reported in those attending for follow up. 51% of all patients had an 8–12 week HIV test (standard 75%). There was 1 new HIV diagnosis reported. Introduction of an ED staff education programme and e-referral pathway has resulted in a 24% increase in patients attending for STI testing. In addition, 100% of patients using pathway had an HIV test within 72 hours and 100% of PEPSE prescriptions were within recommended indications. Discussion: Targeted quality improvement strategies can have a significant impact on PEPSE outcomes for higher risk groups. Improved follow up within GUM after PEPSE prescription in ED has increased opportunities for diagnosis and treatment of STIs, vaccine provision and patient education.